2017
DOI: 10.1016/j.jalz.2017.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Multidomain lifestyle intervention benefits a large elderly population at risk for cognitive decline and dementia regardless of baseline characteristics: The FINGER trial

Abstract: The FINGER intervention was beneficial regardless of participants' characteristics and can thus be implemented in a large elderly population at increased risk for dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
220
0
11

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 297 publications
(239 citation statements)
references
References 28 publications
8
220
0
11
Order By: Relevance
“…Even though the prevalence of carriage of two APOE4 alleles is much lower than the prevalence of Aβ misfolding (in our study: 1.5% vs. 11.0% among controls) and carriers of two APOE4 alleles comprise a very high risk group, the risk associated with Aβ misfolding was found to be stronger than APOE4 status in our study (OR, 23.0, 11.8–44.5). Additional risk stratification strategies and prevention studies have also been based on demographic, health, and lifestyle factors . The presented risk stratification strategy based on Aβ misfolding in blood plasma expressed greater long‐term disease prediction accuracy than APOE4 status or other health and lifestyle risk factors and may therefore be useful in targeting individuals for future research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the prevalence of carriage of two APOE4 alleles is much lower than the prevalence of Aβ misfolding (in our study: 1.5% vs. 11.0% among controls) and carriers of two APOE4 alleles comprise a very high risk group, the risk associated with Aβ misfolding was found to be stronger than APOE4 status in our study (OR, 23.0, 11.8–44.5). Additional risk stratification strategies and prevention studies have also been based on demographic, health, and lifestyle factors . The presented risk stratification strategy based on Aβ misfolding in blood plasma expressed greater long‐term disease prediction accuracy than APOE4 status or other health and lifestyle risk factors and may therefore be useful in targeting individuals for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals at high AD risk identified through plasma could receive additional PET imaging and/or CSF examination while low‐risk individuals could be immediately excluded thereby reducing costs, improving participant experience, and increasing ease. Furthermore, those at high AD risk could potentially be targeted in the future for enhanced preventative strategies including multidomain intervention programs incorporating lifestyle factors and vascular risk management …”
Section: Discussionmentioning
confidence: 99%
“…They are also studying whether intervening on multiple risk factors simultaneously is more effective at reducing risk than addressing a single risk factor. Indeed, one such study, 132 the Finnish Geriatric Intervention Study to Prevent Cognitive Impairment and Disability (FINGER), found that a multidomain lifestyle intervention was associated with beneficial effects on cognitive function in older adults at high risk for cognitive decline and dementia. The success of FINGER has led to the launch of multidomain lifestyle intervention studies in other countries, including the Alzheimer's Association U.S. Study to Protect Brain Health Through Lifestyle Intervention to Reduce Risk (U.S. POINTER) 133 …”
Section: Overview Of Alzheimer's Diseasementioning
confidence: 99%
“…Some clinical trials have demonstrated that multimodal interventions aimed at reducing AD risk, including nutrition, physical activity, cognitive engagement, and management of comorbidities improved cognitive functioning in non-impaired individuals at risk for AD (14, 15). A subgroup analysis of the Finnish Geriatric Intervention Study to Prevent Cognitive Impairment and Disability (FINGER) trial showed that there was no significant difference between the effects of lifestyle modifications on cognitive function in APOE ε4 carriers versus non-carriers (16).…”
Section: Multi-modal Lifestyle Considerationsmentioning
confidence: 99%